Central and Peripheral Cannulation for Cardiopulmonary Bypass in Fetal Sheep: A Comparative Study - Teng, Yun; Tian, Miao; Huang, Bingxin; Wu, Wentao; Jiang, Qiuping; Luo, Xiaokang; Pan, Wei; Zhuang, Jian; Zhou, Chengbin; Chen, Jimei (Frontiers in Cardiovascular Medicine, 2021)
Objective: In-utero correction is an option for treatment of critical congenital heart diseases (CHDs). Fetal cardiac surgery for CHDs is dependent on the reliable use of fetal cardiopulmonary bypass (CPB), but this technology remains experimental. In this study, we established fetal CPB models with central and peripheral cannulation to explore the differences between the two cannulation strategies. Methods: Ten fetal sheep with 90–110 gestational days were randomized into central cannulation (n=5) and peripheral cannulation (n=5) groups. All fetal CPB models were successfully established. At each time point (0 min, 30 min and 60 min after initiation of CPB), echocardiography was performed. Blood samples were also collected for blood gas analysis and tests of myocardial enzymes and liver and kidney function. Results: In the central cannulation group, right ventricular Tei index significantly increased (p=0.016) over time. Compared with the peripheral cannulation group, the left ventricular Tei index of the central cannulation group was significantly higher (1.96±0.31 vs. 0.45±0.19, respectively; p=0.028) and the stroke volume was lower (0.46±0.55 vs. 2.13±0.05, respectively; p=0.008) at 60 min after CPB. Levels of liver and kidney injury markers and of acid-base balance, including alanine aminotransferase (ALT), aspartate aminotransferase/ALT ratio, blood urea nitrogen (BUN), BUN/creatinine ratio, base excess and bicarbonates, were significantly higher for peripheral than for central cannulation. Other important physiologic parameters, including heart rate, blood pressure, myocardial enzymes, umbilical artery beat index and resistance index, left ventricular Tei index, and left and right ventricular stroke volume, were comparable between the two groups. Conclusions: Both central and peripheral cannulations can be used to establish fetal CPB models. Central cannulation causes more adverse impacts for cardiac function, whereas peripheral cannulation is more susceptible to complications related to inadequate organ perfusion.